Investigating the Relationships Between Three Important Functional Tasks Early After Stroke: Movement Characteristics of Sit-To-Stand, Sit-To-Walk, and Walking - Chandler, Elizabeth Ann; Stone, Thomas; Pomeroy, Valerie Moyra; Clark, Allan Brian; Kerr, Andrew; Rowe, Phillip; Ugbolue, Ukadike Chris; Smith, Jessica; Hancock, Nicola Joanne (Frontiers in Neurology, 2021)
Background: Walking, sit-to-stand (STS) and sit-to-walk (STW) are all considered important functional tasks in achieving independence after stroke. Despite knowledge that sensitive measurement of movement patterns is crucial to understanding neuromuscular restitution, there is surprisingly little information available about the detailed biomechanical characteristics of, and relationships between, walking, sit-to-stand and sit-to-walk, particularly in the important time window early after stroke. Hence, here, the study aimed to: 1. To identify the biomechanical characteristics of and determine any differences in both movement fluidity (hesitation, coordination and smoothness) and duration of movement phases, between sit-to-stand (STS) and sit-to-walk (STW) in people early after stroke 2. To determine whether measures of movement fluidity (hesitation, coordination, and smoothness) and movement phases during sit-to-stand (STS) and/or sit-to-walk (STW) are correlated strongly to commonly used measures of walking speed and/or step length ratio in people early after stroke Methods: This study consisted of secondary data analysis from the SWIFT Cast Trial. Specifically, we investigated movement fluidity using established assessments of smoothness, hesitation and coordination and the time duration for specific movement phases in a group of 48 people after stroke. Comparisons were made between STS and STW and relationships to walking measures were explored. Results: Participants spent significantly more time in the initial movement phase, flexion momentum, during STS (mean time (SD) 1.74s ±1.45s) than they did during STW (mean time (SD)1.13s ±1.03s). STS was also completed more smoothly but with more hesitation and greater coordination than the task of STW. No strong relationships were found between movement fluidity or duration with walking speed or step length symmetry. Conclusions: Assessment of movement after stroke requires a range of functional tasks and no one task should predominate over another. Seemingly similar or overlapping tasks such as STS and STW create distinct biomechanical characteristics which can be identified using sensitive, objective measures of fluidity and movement phases but there are no strong relationships between the functional tasks of STS and STW with walking speed or with step-length symmetry.